2022
DOI: 10.47176/jafm.15.01.32832
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Combined Drag Reduction Bases on Vortex Generators and Riblets for the Ahmed Body using IDDES Methodology

Abstract: The flow fields around vehicle drag reduction devices are three-dimensional, complicated, and unsteady. Meanwhile, the small scale of the drag reduction device brings more challenges to the simulation. An Improved Delayed Detached Eddy Simulation (IDDES) was applied to study the effect of two types of drag reduction device. First, the flow field of an Ahmed body at a 25° slant was simulated in detail using IDDES and verified by experiment data. Afterwards, the flow field structures of adding-on vortex generato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It has been reported that the aerodynamic drag of a mid-size car contributes up to 46% of fuel consumption at highway speeds, and a 5% reduction in aerodynamic drag could result in a reduction of 1.5 g/km of CO 2 [1]. Therefore, engineers and scholars have made significant efforts to improve the aerodynamic performance of vehicles using passive and active devices [2,3]. Kim et al argued that the classical approach to reducing drag, such as shape modification, is not feasible in the modern world due to customers' aesthetic demands [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the aerodynamic drag of a mid-size car contributes up to 46% of fuel consumption at highway speeds, and a 5% reduction in aerodynamic drag could result in a reduction of 1.5 g/km of CO 2 [1]. Therefore, engineers and scholars have made significant efforts to improve the aerodynamic performance of vehicles using passive and active devices [2,3]. Kim et al argued that the classical approach to reducing drag, such as shape modification, is not feasible in the modern world due to customers' aesthetic demands [4].…”
Section: Introductionmentioning
confidence: 99%
“…A 6.21% drag reduction was achieved using vg. Finally, 4 combinations of those flow control parts were tested and 8.62% drag reduction was achieved [8]. In another study, excellent hydrodynamic features of tuna were investigated experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…installing devices in specific locations at specific angles, in order to modify the vortices generated in the wake zone: Synthetic jets [7]; Pulsed jets [8], [9], [10], [11]; Steady blowing micro jets at the top edge of slanted surface [12], [13], [14], [15] ; Suction [16], [17], [18] ; Plasma actuators [19] and fluid oscillators [20]. The passive method consists on the use of discrete obstacles, added around or on the roof of the vehicle to change the vortices that are created in the wake zone: Tail plate [21]; Non-smooth surface [22] ; Rear screen and rear fairing [23] ; Underbody device [24] ; Vortex generators on the roof of the model [25], [26], [27]; Streaks [28] ; Jet boat tail [29] ; Rear linking tunnels [30]; Lateral guide vanes [31] ; Underbody diffusers [32], [33], [34] ; Vertical splitter plate [35] and deflector at the edges of the slanted surface and vertical base [36], [37], [38], [39]. Relative to active control, passive control method does not need any sophisticated actuators and electronic control systems, which insures higher reliability.…”
Section: Introductionmentioning
confidence: 99%